Implementasi Model Pembelajaran Ict Dalam Kemampuan Pembelajaran di Kelas Tinggi Siswa di SD Negeri 93 Palembang - Elna Heryani; Nailah Alifah; Dela Irawan; Dira Putri Oktafiyani; Riky Tri Hartady (Jurnal Riset Multidisiplin Edukasi, 2025)
This study aims to describe the implementation of digital literacy and the use of information and communication technology (ICT) in the learning process at SDN 93 Palembang and their impact on student learning abilities in the upper grades. The research method used was descriptive qualitative, with data collection through observations and interviews with teachers and students in grades 4, 5, and 6. The results indicate that the implementation of digital literacy at SDN 93 Palembang has been quite successful. Teachers act as facilitators, actively introducing and guiding students in the wise use of technology. The use of digital media such as projectors, computers, and learning videos helps increase student interest and understanding of the subject matter. ICT facilities at the school are considered adequate, with Chromebooks, projectors, and internet access supporting learning activities. However, challenges remain, such as limited facilities, unstable network connectivity, and low student readiness in using technology. Students' responses to the implementation of ICT have been very positive, as they find learning more engaging, interactive, and easier to understand. Overall, the integration of ICT at SDN 93 Palembang has contributed positively to increasing learning effectiveness, strengthening digital character, and fostering student learning independence.